2023
DOI: 10.1183/13993003.01532-2022
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory recovery trajectories after severe-to-critical COVID-19: a 1-year prospective multicentre study

Abstract: BackgroundSurvivors of severe-to-critical COVID-19 may have functional impairment, radiological sequelae and persistent symptoms requiring prolonged follow-up. This pragmatic study aimed to describe their clinical follow-up and determine their respiratory recovery trajectories, and factors that could influence them and their health-related quality of life.MethodsAdults hospitalised for severe-to-critical COVID-19 were evaluated at 3 months and up to 12 months post-hospital discharge in this prospective, multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
1
20
2
Order By: Relevance
“…Loss of lung units secondary to parenchymal damage with persistent lung consolidations has been demonstrated especially in patients with severe pneumonia in association with reduced D LCO [ 15 , 16 ]. Recently, S chlemmer et al [ 17 ] have reported that during a follow-up of 12 months, >50% of COVID-19 patients still experienced dyspnoea on exertion independent of the severity of the initial disease, and in >40% of the study sample, D LCO showed a mild to severe impairment apparently not secondary to a diffusion defect. A functional loss of V A during tidal breathing and during forced expiration was also observed by S caramuzzo et al [ 10 ] while measuring the regional distribution of ventilation by means of electrical impedance tomography in patients with dyspnoea (mMRC ≥1) 12 months after SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…Loss of lung units secondary to parenchymal damage with persistent lung consolidations has been demonstrated especially in patients with severe pneumonia in association with reduced D LCO [ 15 , 16 ]. Recently, S chlemmer et al [ 17 ] have reported that during a follow-up of 12 months, >50% of COVID-19 patients still experienced dyspnoea on exertion independent of the severity of the initial disease, and in >40% of the study sample, D LCO showed a mild to severe impairment apparently not secondary to a diffusion defect. A functional loss of V A during tidal breathing and during forced expiration was also observed by S caramuzzo et al [ 10 ] while measuring the regional distribution of ventilation by means of electrical impedance tomography in patients with dyspnoea (mMRC ≥1) 12 months after SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…A total of 2517 studies were identified, of which 43 met the inclusion (N = 8858 patients) ( Figure 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The majority of studies were from China (14 studies [ 51 , 58 , 59 , 60 , 61 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…Data on long-term sequelae of severe COVID-19 pneumonia beyond clinical follow-up at six months are scarce [111,112]. Barria Residual dyspnoea was the most common symptom, with a prevalence of 55% ~9 weeks post-infection.…”
Section: Pfts and Imagingmentioning
confidence: 99%